2021
DOI: 10.7717/peerj.10695
|View full text |Cite
|
Sign up to set email alerts
|

Local dynamics of a white syndrome outbreak and changes in the microbial community associated with colonies of the scleractinian brain coral Pseudodiploria strigosa

Abstract: Reef corals in the Mexican Reef System have been severely affected by the emergence of a white syndrome that resembles both White Plague II and SCTLD descriptions. Meandroid scleractinian coral species are among the most severely affected. To gain insight into this affliction we conducted a broad study in the brain coral Pseudodiploria strigosa at a rear reef site in the NE Mexican Caribbean. We describe macro and microscopical signals of the disease, characterize the outbreak dynamics, the tissue histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 84 publications
3
37
1
Order By: Relevance
“…Therefore, this experimental design may have "leveled the playing field, " allowing for equivalent exposure among species to pathogenic material, which may not exist in nature. Histopathological analysis of a small subset of samples from the experiment found similar tissue markers of disease as previous SCTLD studies (Landsberg et al, 2020;Thome et al, 2021), suggesting similar physiological impacts once infected. Diseased samples of all six experimental species showed greater symbiont vacuolization and exocytosis than healthy samples.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, this experimental design may have "leveled the playing field, " allowing for equivalent exposure among species to pathogenic material, which may not exist in nature. Histopathological analysis of a small subset of samples from the experiment found similar tissue markers of disease as previous SCTLD studies (Landsberg et al, 2020;Thome et al, 2021), suggesting similar physiological impacts once infected. Diseased samples of all six experimental species showed greater symbiont vacuolization and exocytosis than healthy samples.…”
Section: Discussionsupporting
confidence: 76%
“…For example, gastrodermal necrosis was found in 87% of visually diseased histological samples as well as in 11% of apparently healthy areas of tissue (Landsberg et al, 2020). And microbial communities on apparently healthy tissue of affected colonies are sometimes similar to those of unaffected colonies while other times more similar to those at active lesions (Meyer et al, 2019;Rosales et al, 2020;Thome et al, 2021). It has also been suggested that the bacteria seen in microbiome studies are purely opportunistic, capitalizing on other underlying health issues (Landsberg et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…3. Thome et al (2021) tagged 96 P. strigosa colonies on an SCTLD-affected reef in Mexico; within 306 days, mortality was greater than 84%, with nearly half of the surviving colonies actively diseased at that point. 4.…”
Section: Random Effectsmentioning
confidence: 99%
“…The spreading spatial patterns have suggested a primary infectious causal agent and diminishing tissue loss rates in affected colonies treated with antibiotics reinforce the idea that a bacterial infection is involved in SCTDL syndrome development (Neely et al, 2020). Nevertheless, so far, although several putative bacterial agents have been proposed (Aeby et al, 2019;Meyer et al, 2019;Paul et al, 2019;Iwanowicz et al, 2020;Thomé et al, 2021) no causality has been demonstrated, only association, which is not evidenced enough (Hill, 1965;Evans, 1976). Moreover, given the above, it seems that opportunistic pathogens may play a confusing role to the extent that Aeby et al (2019) consider that not just bacteria, but viruses or even protozoa may play a causal role in the SCTLD.…”
Section: Introductionmentioning
confidence: 96%